Efisiensi Pasar Bentuk Lemah Era Percepatan Pada Saham Sektor Properti di BEI - Ayni Witia; Nurhikma Nurhikma; Ina Annisa; Astutianti Afnur; Nurabidah Nurabidah; Suriani M; Dian Firmayasari S (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to examine weak-form market efficiency in property sector stocks based on stock return movements during the era of accelerated information dissemination, marked by the year 2020 when the Covid-19 pandemic accelerated digital transformation in the capital market, resulting in faster information dissemination and stock trading processes. Weak-form market efficiency assumes that historical information is fully reflected in stock prices. The property sector was selected due to its characteristics as a sector with relatively low liquidity and unstable trading volume. These conditions may prevent stock prices from fully reflecting information in a timely manner, thereby creating the potential for market inefficiency. This study employed a sample of eight property sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period, selected using purposive sampling. Stock returns were analyzed using the Augmented Dickey-Fuller (ADF) test, Ljung-Box test, Jarque-Bera test, and Run Test to identify the presence of patterns or dependencies in historical data. The results indicate that property sector stocks have not fully satisfied the criteria of weak-form market efficiency, as efficiency was only observed partially and not uniformly across all sampled stocks. These findings are supported by the Run Test results, which show that the majority of stocks do not follow a random pattern, although the ADF and Ljung-Box tests indicate evidence of efficiency in certain aspects. This suggests that past stock price information has not entirely lost its relevance and that, under certain conditions, investors may still use historical information to predict stock returns.